Development of a Website-Based Application for Aspirations for the Kalibagor Village Community Using the Extreme Programming Method: Pengembangan Aplikasi Wadah Aspirasi Masyarakat Desa Kalibagor Berbasis Website Dengan Metode Extreme Programming - Pradana Ananda Raharja; Luqman Fattah Nadin (Universitas Muhammadiyah Purworejo, 2022)
Community service is a task that the government must carry out. However, community services in Kalibagor Village, especially in responding to aspirations and complaints, are done manually using written media and submitted through the media suggestion box. One factor that influences the delivery of aspirations is the time and distance between the house and the village office as a barrier for the community to express their aspirations. Based on these problems, Kalibagor Village accommodates to make it easier for the district to express its aspirations, criticism, and suggestions. The website-based application for the aspirations of the Kalibagor Village community is a solution to overcome the problems described. The extreme Programming method is a method for developing this application. Based on this research, it produces an aspiration container application that can accommodate aspirations, criticisms, and suggestions, users can also like or like aspirations and comment on submitted aspirations, and there is an admin to manage information and user data in the community aspiration container application. Based on the test results using the black-box testing method, the average value of 100% is in a suitable category. So, the application of this community aspiration container is ideal for use by village officials in providing services for aspirations and the community.